An Investigation into the Clinical Utility of Transfer Functions between the Aortic and Femoral Pressure Waveforms. Issue 27 (2018) - Davidson, Shaun M.; Pretty, Chris; Balmer, Joel; Desaive, Thomas; Chase, J. Geoffrey
Abstract: Management of cardiovascular disease in intensive care would benefit from improved methods for data from clinically available, information rich arterial pressure waveforms. This paper explores the feasibility of using the transfer function between the aortic and femoral pressure waveforms as a diagnostic tool, over an experimental cohort including the progression of sepsis. Transfer functions appeared as physiologically expected, with Bode plot peaks near breathing and heartbeat frequencies. The Bode plot response to clinical interventions and disease progression also matched physiological expectations, with peaks increasing in magnitude in response to fluid infusion and attenuating in response to the progression of sepsis. While there are clear potential diagnostic benefits to the approach, further work is needed to make this information easier to rapidly interpret in a clinical environment, and to evaluate the specificity of the transfer function responses presented here to the progression of sepsis.